Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.